Mental imagery in chronic pain: Prevalence and characteristics. (17th October 2013) - Gosden, T.; Morris, P.G.; Ferreira, N.B.; Grady, C.; Gillanders, D.T.
Abstract Background Research into mental imagery has increased our understanding of a range of psychological problems. However, there has been little study into the spontaneous mental images experienced in response to chronic pain. This study aimed to explore the prevalence and characteristics of these pain‐related mental images. Methods Four hundred ninety‐one people with chronic pain who had attended a pain clinic were sent invites to participate and 105 people responded (21%). A mixed‐methods approach (quantitative and qualitative) was used to explore the prevalence of pain‐related mental imagery, differences between imagers and non‐imagers, and the content of imagery in pain. Results In our sample, 36% of respondents reported having mental images of their pain, with the majority describing them as clear and vivid (83%), experienced daily (80.5%), and distressing (83%). Participants who experienced mental images reported higher depression scores, higher anxiety and higher pain unpleasantness. Frequency of imagery was associated with greater pain unpleasantness. Content analysis of the pain images revealed emerging themes relating to the sensory qualities of pain, anatomical representations, pain as a form of threat or attack, pain as an object, and pain as an abstract image. Conclusions This study describes themes and characteristics of pain‐related mental imagery and confirms that they are a frequent, vivid and distressing experience for many chronic pain sufferers. The results of this study suggest that pain‐related mental imagery could provide an additional route for assessment and intervention. Further research should focus on assessment, measurement and intervention in clinical populations.